Periodontal health status of people with dementia – A systematic review of case-control studies - N. Ab Malik; A.W.G. Walls (Saudi Dental Journal)
Background: The number of older people increases globally, so is the risk of cognitive impairment. Periodontal diseases are common among older adults with significant tooth loss and periodontal problems. Thus, this review explored the periodontal disease conditions among individuals with and without dementia. Methods: Available databases such as Medline/Pubmed, Web of Science, Scopus, Cochrane Library and Embase/OVID were used in the search. Case-control studies reporting on periodontal disease and dementia parameters were selected based on PICO (Population, Intervention, Comparison and Outcomes) framework. A Newcastle-Ottawa Scale (NOS) was used to assess the quality reporting of the studies and PRISMA guideline was used for screening. Results: A total of ten studies were identified for analysis. Most studies reported higher plaque index score (PI), bleeding on probing (BoP), pocket depth (PD) and clinical attachment loss (CAL) among individuals diagnosed with dementia or Alzheimer’s disease compared with clinically healthy controls or individual diagnosed without dementia. A higher prevalence of subjects with severe periodontal disease was also observed in individuals diagnosed with dementia/Alzheimer’s disease. The quality of the studies was found to be moderate with lower comparability and ascertainment criteria scores. Conclusion: This qualitative analysis has shown poor periodontal health and increased inflammatory mediators in case groups compared to the control groups. Thus, more quality studies and novel intervention are warranted to reduce the impact of periodontal health on dementia globally.